Comparison of cost and return for durian farmers on Magik Growth wrapping bag innovation to increase the quality of durian production in Rayong Province, Thailand - Thongtem, K.; Suwanmaneepong, S.; Suwunnamek, N.; Kerdsriserm, C. (My University, 2025)
The results of the study revealed that farmers who did not use the Magik Growth durian wrapping bag innovation had total costs of 37,647.48 baht per rai, resulting in an average yield of 1,420.41 kilograms per rai and a net profit of 164,999.25 baht per rai. In contrast, farmers who used the Magik Growth durian wrapping innovation had total costs of 48,724.58 baht per rai, leading to an average yield of 1,420.83 kilograms per rai and a net profit of 195,068.58 baht per rai. There was a significant difference of 0.01 in the average yield between those using and not using the Magik Growth durian wrapping innovation. Fixed costs and break-even yield also showed a statistically significant difference at 0.05. However, total costs, variable costs, production factors, product prices, net profit, and prices showed no statistically significant difference.
Keywords: Cost and return; Durian; Magik Growth